Desenvolvimento de um sistema supervisório aplicado em uma usina de geração de energia solar fotovoltaica - Melo, Anderson Rodrigues de (Universidade Federal Rural do Semi-Árido, 2020)
The increase demand for electric energy due to the improvement in the quality of life has stimulated the demand for alternative renewable energy sources that, in addition to providing energy benefits, also reduce environmental impacts. Photovoltaic solar energy, for example, has played a prominent role in recent years, primarily in the generation of electricity. However, the use of this form of energy depends on several factors, the main one being the solar radiation on photovoltaic modules. Measuring the energy generated by a solar photovoltaic system is essential when it is desired to identify the efficiency rate or the existence of failures. Therefore, predictive measurements allow to increase the efficiency of the system, since the continuous monitoring optimizes the operation and identifies the need for its maintenance. Therefore, this work aims to apply Internet of Things (IoT) to perform the measurement of electrical parameters generated by an inverter operating in a solar photovoltaic plant at the Federal Rural University of the Semi-Arid (UFERSA), since it does not have a supervisory system, that is, it does not provide the desired monitoring. In this context, an IoT-based device was developed to measure the energy generated by the photovoltaic solar plant, to make data available in real time, as well as the history through a supervisory system. Tests were carried out in order to evaluate the accuracy and the communication interface of the prototype, where it proved to be efficient in both aspects
Keywords: Geração fotovoltaica; IoT; Medição de energia elétrica; Sistema supervisório; Blynk®; Photovoltaic generation; IoT; Electricity measurement; Supervisory system; Blynk®; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA